MASKED HYPERTENSION INCIDENCE: RISK FACTORS IN A PROSPECTIVE COHORT STUDY. (June 2018) - Xavier, T.; Brisson, C.; Gilbert-Ouimet, M.; Duchaine, C.; Dalens, V.; Talbot, D.; Milot, A.
Abstract : Objective: Masked hypertension affects approximately 10 to 20% of the general population and is associated with a higher risk of cardiovascular diseases. No previous prospective study has examined risk factors associated with masked hypertension incidence. The aim of this study was to examine risk factors associated with masked hypertension incidence in a prospective cohort from Quebec City, Canada. Design and method: This is a dynamic cohort study using two pooled longitudinal samples of initially normotensive participants (Year 0 – Year 3; Year 3 – Year 5). The study sample was composed of 1, 836 participants. At each time, blood pressure (BP) was measured using Spacelabs 90207. Manual BP was defined as the mean of the first three readings taken at rest. Ambulatory BP was defined as the mean of the next readings recorded every 15 minutes during daytime working hours. Risk factors of masked hypertension incidence were examined using cross-lagged generalized estimating equations. Results: After mutual adjustment, masked hypertension incidence was associated with male gender (RR = 1.53, 95% CI: 1.19–1.96), age (RR40–49 = 1.55, 95% CI: 1.14–2.10; RR > = 50 = 1.48, 95% CI: 1.05–2.09), body mass index (RR> = 27 = 1.45, 95% CI: 1.12–1.87), smoking status (RR = 1.49, 95% CI: 1.07–2.08) and alcohol intake (RR> = 6/week = 1.46, 95% CI: 1.06–2.00). Conclusions: Findings point toward sociodemographic and lifestyle related risk factors associated with masked hypertension incidence. These factors should be considered in screening efforts of individuals at risk for developing masked hypertension.